Diseño e implementación de un vehículo de transporte giroscópico eléctrico Sedway, con auto balanceo controlado por un sistema embebido con arquitectura ARM. - Quinteros Jaramillo, Guillermo Rodrigo (2016)
In the present project detailing the processes of design, implementation and configuration of a transport vehicle electrical gyro segway, with auto controlled balancing by an embedded system with arm architecture, the goal of this work is the development of the part of vehicle stability control through mechanical conditions and programming. The vehicle is based on the principle of an inverted pendulum, giving the power to move to compensate for the displacement of the pendulum by holding it in balance. Shall be determined an electronic card to carry out the processes of arm architecture, as well as the autonomy of electric batteries, motors and power of a control system that allows us to manage the speed that the vehicle will go, all of this based on the prototypes segway globalising knowledge and theory of instrumentation, Control Theory and Industrial Computing, studied in the career of Electronic Engineering of the UPS headquarters Quito-Campus South, obtaining as a result end a unipersonal sophisticated transport that allows mobilized quickly optimizing time and physical effort